Association between sprint and jump performance and maximum strength in standing calf raise or squat in elite youth soccer players - Kadlubowski, B.; Keiner, M.; Wirth, K.; Csapo, R. (Sports, 2024)
Soccer is a complex sports discipline that requires players to engage in diverse high-intensity and multidirectional activities. The optimization of strength and conditioning programs requires a comprehensive understanding of the physical attributes influencing player performance. While previous research has demonstrated the influence of knee and hip extensor muscles on the performance in sprints and other explosive movements, this study aimed to establish the relationship between plantar flexor muscle strength and high-intensity actions. Back squat (BS) and calf raise (CR) one-repetition maxima as well as linear sprint (5-, 10-, 30 m) and drop jump performance from different heights (15, 30, 45 and 60 cm) were measured in 45 elite youth players (age: 16.62 ± 1.1 years). Results showed significant negative correlations between BS strength and sprint times (r = -0.60 to -0.61), confirming the importance of lower limb extensor muscle strength in short-distance sprints. While no significant correlations were found with sprint performances, CR strength was significantly associated with drop jump test results from 45 and 60 cm drop height (r = 0.36 to 0.46). These findings demonstrate that isolated CR strength positively influences the performance in actions involving rapid stretch-shortening cycles, which suggests that current strength and conditioning programs for youth soccer players should be extended to also include exercises specifically targeting the plantar flexor muscles. While this cross-sectional study provides novel insights into the complex interplay between muscle strength and soccer-specific performance, its findings need to be corroborated in longitudinal studies directly testing the impact of plantar flexor strength training.